2016
DOI: 10.1002/smi.2689
|View full text |Cite
|
Sign up to set email alerts
|

Grin and Bear It?: Employees' Use of Surface Acting During Co‐worker Conflict

Abstract: Using survey data from 459 employed individuals, the conditional indirect effects of three types of interpersonal conflict at work on strains and performance through surface acting were tested. Results indicated that task, relationship and non-task organizational conflict were positively related to depressive and physical symptoms and negatively related to performance. Task conflict had a significantly weaker association with employee outcomes than either relationship or non-task organizational conflict. Surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Second, although emotional labor is conceptualized as stemming from interactions with citizens or clients, past studies measured global stressors, with no specific reference to citizens or clients. This may lead to confounding effects, as these measures may capture emotional regulation caused by interpersonal conflicts within the organization, such as with supervisors or coworkers (Nixon, Bruk-Lee, & Spector, 2017). Finally, few studies on police burnout have accounted for officers’ ability to regulate emotions (see Schaible & Gecas, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Second, although emotional labor is conceptualized as stemming from interactions with citizens or clients, past studies measured global stressors, with no specific reference to citizens or clients. This may lead to confounding effects, as these measures may capture emotional regulation caused by interpersonal conflicts within the organization, such as with supervisors or coworkers (Nixon, Bruk-Lee, & Spector, 2017). Finally, few studies on police burnout have accounted for officers’ ability to regulate emotions (see Schaible & Gecas, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Findings showed that those engaging in surface acting toward coworkers suffered from higher emotional exhaustion and lower job performance. Similarly, Hu and Shi (2015) as well as Nixon et al (2017) found negative outcomes of surface acting toward coworkers, including impaired relationships with coworkers and physical symptoms. Further studies extended these findings to group meetings, showing a negative relationship between surface acting toward coworkers in meetings and meeting effectiveness (Shanock et al, 2013; Thomas et al, 2018).…”
Section: Emotional Labor Toward Coworkersmentioning
confidence: 88%
“…Interpersonal conflict is a social stressor that measures disagreements between parties (Spector & Jex, 1998), and has been discussed under the broader workplace aggression construct, comprised of variables such as incivility, bullying, social undermining, and abusive supervision that vary across several defining characteristics, including intensity (Hershcovis, 2011). Interpersonal conflict has been linked to decreased job satisfaction (Ilies, Johnson, Judge, & Keeney, 2011), low performance (Mulki et al., 2015; Nixon, Bruk‐Lee, & Spector, 2017), high turnover intentions (Frone, 2000), stress (Mulki et al., 2015), and physical health symptoms (Nixon et al., 2011, 2017).…”
Section: Introductionmentioning
confidence: 99%